'House to let': housing agents, social networks and Ghana's housing law and policy. Issue 3 (2nd July 2020) - Ansah, John Windie; Takyiakwaa, Dorothy; Atakora, Edward; Amoah, Michael
Abstract: This paper explores the entanglements between housing agents, their social networks and the current rental housing regulatory framework in Ghana. Using purely qualitative methods, the paper sought primary data from 42 housing agents, one Rent Control Department officer, 10 landlords and 15 tenants, and secondary data from government related policies and reports to uncover the nuances of housing agency in Ghana and their relevance to the housing regulatory and policy frameworks. Using narrative analysis, we draw on the social capital theory to uncover how social networks, trust and norms of reciprocity shape activities and strategies of housing agents towards both productive and conflict ridden outcomes. The paper argues that the organisation of activities of housing agents is an exercise of power mobilised through an elaborately informal but orderly social networks underlined by social trust and norms. We contend that such patterns of activities of housing agents founded on the elements of social capital produce both economic and administrative values to the state which could be adapted, refined and incorporated into the current housing regulations and policy.